ANALISIS DAMPAK KEHADIRAN RITEL MODERN TERHADAP RITEL TRADISIONAL DI KOTA MEDAN Studi Kasus Kehadiran Ritel Indomaret di Empat Kecamatan Kota Medan - Ema Yohanna Sihombing; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2013)
The purposes of this research is to analyze the aftermath of the modern retails attendance to the existence of traditional retails, for the case study on four subdistricts of Medan. The data used in this study were obtained from 66 traditional retails on sudistrict Medan Area, subdistrict Medan Helvetia, subdistrict Medan Timur, and subdistrict Medan Johor, by simple random sampling. The analysis method used in this study is Quantitative Descriptive Analysis by Mc Nemar test. The test of validity and reliability of the instrument based on r table value by 0,5%. The result shows that Indomaret Retails significantly affect the omzet of traditional retails, as it significantly influence the traditional retailer in taking strategic initiative on price and retail neatness improvement for retain. Conversely Indomaret Retails attendance neither significantly influence the traditional retailer in taking strategic initiative on retail services, product differemtiation, retail’s working hour, nor the retail interior improvement as well.Keywords : traditional retail, modern retail, omzet, retail strategy